Pengaruh Profitabilitas, Likuiditas dan Firm Size terhadap Struktur Modal (Studi pada Perusahaan Real Estate dan Properti yang Terdaftar di BEI, Periode 2020-2022) - Tamara, Kasih; Inuzula, Lakharis; Muttaqim, Hakim (Singkite Journal, 2024)
This research delves into the intricate dynamics of capital structure decisions within the context of real estate and property companies listed on the Indonesia Stock Exchange (IDX) during the period spanning from 2020-2022. With the aim of examining the interaction between profitability, liquidity and liquidity. and firm size, and its impact on the capital structure choices made by these companies. Using secondary data from the official IDX website and panel regression analysis methods, to provide a comprehensive understanding of how profitability, liquidity and company size collectively influence capital structure decisions of real estate and property companies in Indonesia. The results found that, simultaneously and partially, the variables profitability (RPA), liquidity (Current Ratio) and firm size had a significant effect on capital structure for the next one year period.